Salt Stress Alleviation in Triticum aestivum Through Primary and Secondary Metabolites Modulation by Aspergillus terreus BTK-1 - Khan, Muhammad Ikram; Ali, Niaz; Jan, Gul; Hamayun, Muhammad; Jan, Farzana Gul; Iqbal, Amjad; Hussain, Anwar; Lee, In-Jung (Frontiers in Plant Science, 2022)
We report the growth promoting potential in wheat under saline conditions by an endophytic fungus Aspergillus terreus BTK-1. The isolated BTK-1 from the root of Chenopodium album identified as Aspergillus terreus through 18S rDNA sequence analysis. BTK-1 secreted indole acetic acid (IAA), exhibited 1- aminocyclopropane-1- carboxylate deaminase (ACC) and siderophores activity, and solubilized phosphate. Wheat seedlings exposed to saline environment (0 mM, 60 mM, 120 mM, 180 mM) with or without BKT-1 inoculation. Seedlings inoculated with BTK-1 showed higher concentrations of IAA and GAs, whereas low concentrations of ABA compared to the BTK-1 non-inoculated plants. Also, BTK-1 inoculated wheat plants revealed significantly (P=0.05) longer shoots and roots, biomass and chlorophyll contents. On the contrary, plants without BTK-1 inoculation indicated significantly (P=0.05) low amounts of carbohydrates, phenolics, prolines, potassium, magnesium and calcium, while high amounts of Na and MDA under salt stress. Likewise, BTK-1 inoculated wheat plants showed high activity of reduced glutathione, and low activity of ascorbate, catalase and peroxidase under salt stress. The mitigation of salinity stress by BTK-1 inoculated wheat plants suggested its use as bio-stimulator in salt affected soils.